Effectiveness of individualized home-based exercise on turning and balance performance among adults older than 50 yrs: a randomized controlled trial - Ashari, Asmidawati; Tengku Abdul Hamid, Tengku Aizan; Hussain, Mohd Rizal; Hill, Keith David (Lippincott Williams & Wilkins, 2016)
Objective: This study evaluated the effectiveness of an individualized home-based exercise program that included specific turning exercises in improving turning performance in adults identified as having unsteadiness during turning. Design: A single-blind (assessors) randomized controlled trial was conducted with 68 community-dwelling Malaysians aged 50 yrs and older, who had abnormal turning performance (outside of age and sex, normal limits on the Step/Quick Turn Test [180-degree turn task on the NeuroCom Balance Master with long plate]). The intervention group received a 16-wk home exercise program that included two turning exercises, whereas the control group maintained their usual activities. Results: Significant group × time effects were found using two-way repeated-measures analysis of variance for turning and balance/mobility measures. The intervention group significantly improved relative to the control group for (1) sway when turning 180 degrees Step/Quick Turn, F1,65 = 8.070, P = 0.006; (2) time to perform 180-degree turn Step/Quick Turn, F1,65 = 8.216, P = 0.006; (3) Timed Up and Go (single task), F1,65 = 6.647, P = 0.012; (4) Timed Up and Go (dual task), F1,65 = 8.301, P = 0.005; and (5) static stance sway, F1,65 = 10.491, P = 0.002. Conclusions: An individualized home exercise program that included specific exercises to improve turning ability was effective in improving turning performance in adults older than 50 yrs.